Frontiers in Algorithmics Second Annual International Workshop, FAW 2008, Changsha, China, June 19-21, 2008, Proceeedings - Preparata, Franco P.; Wu, Xiaodong; Yin, Jianping; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the Second International Frontiers of Algorithmics Workshop, FAW 2008, held in Changsha, China, in June 2008. The 33 revised full papers presented together with the abstracts of 3 invited talks were carefully reviewed and selected from 80 submissions. The papers were selected for 9 special focus tracks in the areas of biomedical informatics, discrete structures, geometric information processing and communication, games and incentive analysis, graph algorithms, internet algorithms and protocols, parameterized algorithms, design and analysis of heuristics, approximate and online algorithms, and machine learning.
Fixed Point Computation and Equilibrium -- Computer Science in the Information Age -- Knowledge-Based Approaches to Quantitative Medical Image Analysis and Image-Based Decision Making -- Optimal Field Splitting, with Applications in Intensity-Modulated Radiation Therapy -- A Practical Parameterized Algorithm for Weighted Minimum Letter Flips Model of the Individual Haplotyping Problem -- SlopeMiner: An Improved Method for Mining Subtle Signals in Time Course Microarray Data -- A PTAS for the k-Consensus Structures Problem Under Euclidean Squared Distance -- Haplotype Assembly from Weighted SNP Fragments and Related Genotype Information -- Estimating Hybrid Frequency Moments of Data Streams -- Constraint Bipartite Vertex Cover Simpler Exact Algorithms and Implementations -- NP-Completeness of (k-SAT,r-UNk-SAT) and (LSAT???k ,r-UNLSAT???k ) -- Absorbing Random Walks and the NAE2SAT Problem -- Versioning Tree Structures by Path-Merging -- A Linear In-situ Algorithm for the Power of Cyclic Permutation -- Multi-bidding Strategy in Sponsored Keyword Auction -- A CSP-Based Approach for Solving Parity Game -- Characterizing and Computing Minimal Cograph Completions -- Efficient First-Order Model-Checking Using Short Labels -- Matching for Graphs of Bounded Degree -- Searching Trees with Sources and Targets -- Ranking of Closeness Centrality for Large-Scale Social Networks -- Mixed Search Number of Permutation Graphs -- The 2-Terminal-Set Path Cover Problem and Its Polynomial Solution on Cographs -- A Distributed Algorithm to Approximate Node-Weighted Minimum ?-Connected (?,k)-Coverage in Dense Sensor Networks -- Optimal Surface Flattening -- Visiting a Polygon on the Optimal Way to a Query Point -- Constraint Abstraction in Verification of Security Protocols -- Fast Convergence of Variable-Structure Congestion Control Protocol with Explicit Precise Feedback -- Applying a New Grid-Based Elitist-Reserving Strategy to EMO Archive Algorithms -- The Parameterized Complexity of the Rectangle Stabbing Problem and Its Variants -- Solving Medium-Density Subset Sum Problems in Expected Polynomial Time: An Enumeration Approach -- A Scalable Algorithm for Graph-Based Active Learning -- A Supervised Feature Extraction Algorithm for Multi-class -- An Incremental Feature Learning Algorithm Based on Least Square Support Vector Machine -- A Novel Wavelet Image Fusion Algorithm Based on Chaotic Neural Network.
Keywords: Computer science; Computer programming; Algorithms; Numerical analysis; Computer science -- Mathematics; Computer graphics; Bioinformatics; Computer Science; Programming Techniques; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Computer Graphics; Computational Biology/Bioinformatics.; Electronic books